The Effect of Service Quality, Price, and Location on Customer Loyalty through Customer Satisfaction - Imel, Imel; Nurjannah, Nurjannah; Munawir, Munawir (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2024)
This study aims to determine the effect of service quality, price and location on customer loyalty through customer satisfaction as an intervening variable at Daily Coffee, Palopo, South Sulawesi, Indonesia. The sample in this study amounted to 105 people. The types and sources of data used in this study are qualitative and quantitative data types. Data collection used in this study by conducting observations and questionnaires. Primary data in this study is data obtained from respondents' responses to the statement items he asked in the questionnaire which were obtained either directly or indirectly while secondary data in this study is a source that does not directly provide data to data collectors, for example documents and interviews. The data collected was then analyzed using multiple regression analysis methods with the help of the Smart-PLS program. The results showed that service quality, price and location on customer loyalty through customer satisfaction as an intervening variable at Daily Coffee Palopo, which means that the hypothesis in this study is accepted.